Producing Goods and Projecting Power: How What You Make Influences What You Take. (July 2019) - Markowitz, Jonathan; Fariss, Christopher; McMahon, R. Blake
How does a state's source of wealth condition the domain in which it seeks to project influence? We argue that what a state makes conditions what they take. Specifically, the less states rely on land rents to acquire wealth, the less interested they will be in seeking control over territory and the more interested they will be in securing access to distant markets. We develop and test several observable implications that should follow whether this proposition is true. First, as states become less economically dependent on territory, they should be less likely to fight over territory; second, those states should be more likely to both invest in power projection capabilities and subsequently project power at greater distances. Our findings support our theory. These results are robust across a variety of model specifications that take into account potential confounds, such as regime type, economic development, threat, and geography.